EFISIENSI DAN AKURASI COMPUTERIZED ADAPTIVE TESTING PADA SISTEM UJIAN AKHIR SEMESTER UNIVERSITAS TERBUKA - Agus Santoso (LPPM Universitas Terbuka, 2010)
Universitas Terbuka (UT) applied online examination system (sistem ujian online SUO) for end of semester examination (ujian akhir semester-UAS), beside the paper and pencil test (P & P test). In order to improve efficiency, adaptive test application should be analyzed, as an alternative to present UAS system. The aim of the research was to compare the efficiency and accuracy level of the computerized adaptive testing (CAT) design and conventional test using both P & P test and SUO. The research was conducted by simulation procedure. The item bank for the simulation used calibrated 404 test items using item response theory model. In the research, CAT and P & P test algorithm was developed. To measure efficiency, the required number of the CAT design was analyzed, while to measure accuracy of the estimation, the bias and standard error of measurement of both design were compared. The simulation result showed that (1) CAT design was more efficient, since it required only half of the number of item which was used in P & P test, to estimate the ability of examinee, (2) CAT design was more accurate in estimating ability of examinee, compared to P & P test design, since it resulted lower bias and standard error of measurement compared to conventional test design. Therefore, CAT design could be applied in UTs UAS system, while considering the balance of content for each modules.